Shift to private pension system: The case of Poland and Israel - Manor, Moshe; Ratajczak, Joanna (DEMO, 2020)
Following Chilean experiences as well as the World Bank suggestions post‑communist Poland and post-collectivist Israel—underwent deep reforms which led to the privatization of old age security. The aim of the article is to compare the Polish and Israeli paths of pension privatization in the last thirty years. The main conclusions are: (1) the economic, demographic and political environments at the moment of the design and implementation of the pension reform were quite similar in both countries; however (2) the scope and scale of the privatization was different: in Poland there was only partial shift towards private pension system while in Israel full privatization of the system was implemented; (3) the decisive factors were: the inertia of the already existing pension systems and the power of foreign influencers; (4) the retreat from privatization in Poland and the increase in Israel took place due to the different mix of disadvantages of the new pension arrangements, short-term political aims and international pressure.